The Implementation of Religious Moderation in the Public University of Malang - Rohmat Mulyana Sapdi; Novia Elok Rahma Hayati; Nur Ali (J-PAI: Jurnal Pendidikan Agama Islam, 2022)
Religious moderation has become a new trend upon conflict and intolerance resolution among religious communities, especially in Indonesian universities. This paper aims to explain the process of implementing religious moderation to enhance appropriate socio-religious attitudes and religious tolerance at Universitas Merdeka Malang. It is a case study with an in-depth interview followed by observation and documentation study. This study finds that the implementation of religious moderation is carried out in 3 stages, namely (1) coordination meetings of lecturers in the religious study forum (RSA) to discuss lecture material, (2) Preparation of RPS or Rencana Pembelajaran Semester or syllabus by including religious moderation material, (3) applying religious moderation through (a) religious education lecture, citizenship education, and religious enrichment. (b) off-campus classroom through (i) students’ religious activity units (SAU), including Jubilee SAU (Christian), Loyola SAU (Catholic), Alhuda SAU (Islamic) and Dharma WTC SAU (Hindu). Non-Muslim religious activities can be carried out at the mosque since this is the center of worship building on campus, (ii) activating a student’ council Instagram account for broadcasting information about religious moderation, and the existence of local cultures to represent national commitment and accommodative attitudes towards local cultures.